Fundamentals of Entrepreneurship : Groovy Tartlet / Che Wan Nursyakira Che Wan Nazami ... [et al.] - Che Wan Nazami, Che Wan Nursyakira; Mohd Karim, Khairunnisa; Hashim Azmi, Nukhadija; Ruslan, Nurulikmila; Abu Baicar, Nuraslinda (2011)
Groovy Tarlet Enterprise is a name of our company that sold a variety of tarts. Groovy mean passion, something sweet that can enhance our appetite. In other words, when tarts comes into your mouth, you can feel the combination of crispiness, sweetness and creamy. Our tarts blend the world of sweet savory by using innovative, unexpected ingredients our customers adore. Freshness is key which is why we make our products to order. The quality of our ingredients is our primary concern. Groovy Tarlet is a name of our new company that want to commercialize and to introduce the new flavor and variety of tarts. The name of Groovy Tarlet give effect to our customers that they easily to recognize our product’s company. Our business organization is based on partnership. It’s form from five young ladies who are agreeing to contribute their own capital and times in order to operate our business. We had delegated the responsibilities of managing and handling the task among our partnership. The main purpose of our business is to introduce new variety flavor of tarts. Now days it is difficult to find flavored tart in the market. So, this is the reason why we had come with new idea. For future prospects of our business we hope that the products will be accepted well by the customers and get good feedback from them. We are also hoping that, our product will be export in overseas markets.